When you were born - Aston, Dianna Hutts; Lewis, Earl B. (Cambridge, Mass. Candlewick Press, 2004)
A mother describes the joyful time of her baby's birth and how it was celebrated by family and neighbors.
Keywords: Babies -- Fiction; Mother and child -- Fiction